Hyposmia in geriatric depression can be a meningioma - Muruganandam Partheeban (Journal of Geriatric Mental Health, 2019)
Depression in the elderly population can be a manifestation of underlying neurological and systemic disorder. It can be harbinger in many neurological illnesses such as Parkinson's disease and Alzheimer's dementia. It can present as early as 10 years before the onset of clinical neurological signs in dementia. Brain tumors can present with varying psychiatric symptoms such as depression, anxiety, cognitive or personality changes, or schizophrenia. Olfactory groove meningioma is uncommon benign brain tumor which accounts for <10% of all intracranial meningiomas. Olfactory meningioma, which occurs in the anterior cranial fossa, can compress the frontal lobe, thereby rarely present only as depressive symptoms in the absence of neurological symptoms. The present case report illustrates depression with hyposmia in elderly women, which unmasked the giant olfactory groove meningioma and significant improvement in depressive symptoms following surgical resection.